Short communication. First report in Cuba of bovine coronavirus detection in a winter dysentery outbreak - Barrera Valle, M.; Rodríguez Batista, E.; Betancourt Martell, A.; Frías Lepuroux, M. T.; Brandão, P. (Spanish Journal of Agricultural Research, 2006)
Bovine coronavirus (BCoV) infection causes epidemics of acute diarrhea in calves and winter dysentery (WD) in adult cattle. The disease in adult cattle can cause a decrease in milk production resulting in serious economic losses. In Cuba, BCoV infections have not been previously reported. During 2004, many outbreaks of enteric disease have occurred in adult cattle from thirteen dairy farms in the central and western part of the island. The clinical features of the outbreaks resembled those of WD, such as decrease in milk production and, 24 hours later, diarrhea, sometimes bloody, that lasted until the animals recovered in about 7-15 days. Laboratory confirmation of BCoV infection was provided by hemagglutination test (HAT) in 24 samples from four dairy farms from three provinces; RT-PCR assays confirmed the presence of BCoV in three of these samples. Cell culture isolation in secondary calf kidney cells was obtained from four pools of fecal diarrheic samples from each dairy farm. It was remarkable that the disease was also observed during summer. Studies of molecular characterization of the viral strain are in progress.